2011
DOI: 10.1007/s12011-011-9057-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of l-Selenomethionine and Selenite by Probiotic Bacteria: In Vitro and In Vivo Studies

Abstract: Since selenium supplements have been shown to undergo biotransformation in the gut, probiotic treatment in combination with selenium supplements may change selenium disposition. We investigated the metabolism of L-selenomethionine (SeMet) and selenite by probiotic bacteria in vitro and the disposition of selenium after probiotic treatment followed by oral dosing with SeMet and selenite in rats. When SeMet was incubated anaerobically with individual antibiotic-resistant probiotic strains (Streptococcus salivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Indiscriminate use of dietary Se supplements, even at doses recently considered to be safe may lead to severely affected redox status with subsequent adverse health effects, as also suggested by an increasing body of epidemiologic evidence. Moreover, Se has other effects yet uninvestigated, for example the potential of epigenetic regulation of DNA and histones [251][252][253] or interaction with the gut microbiota [254][255][256], which need to be carefully addressed. At the same time, the unclear interactions between Se and heavy metals also need clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Indiscriminate use of dietary Se supplements, even at doses recently considered to be safe may lead to severely affected redox status with subsequent adverse health effects, as also suggested by an increasing body of epidemiologic evidence. Moreover, Se has other effects yet uninvestigated, for example the potential of epigenetic regulation of DNA and histones [251][252][253] or interaction with the gut microbiota [254][255][256], which need to be carefully addressed. At the same time, the unclear interactions between Se and heavy metals also need clarification.…”
Section: Discussionmentioning
confidence: 99%
“…This means that part of the supplemented selenium would have passed though different routes in addition to replenishing the serum component. Among such possible selenium channeling routes may include, excretion [54]; metabolism by gut biota to forms that reduce absorption into circulation [55]; used up for toxicity modulation [56]; channeled towards other tissue optimization [57] including that of the prostate [58][59][60]; or the selenomethionine component in the selenized yeast [61] getting non-specifically incorporated into a wide range of tissue proteins in place of methionine [62,63]. Takata et al, 2009 have shown that serum selenium level is a reflection of the levels in the prostate [59].…”
Section: Discussionmentioning
confidence: 99%
“…Sham-treated rats received 50 μL of vehicle alone. In addition, rats received an oral dose of SeMet (2 mg SeMet/kg body weight/day) according to methods described in previous studies [ 26 , 27 ]. All rats were sacrificed three weeks after the final injection of CoNPs or vehicle alone.…”
Section: Methodsmentioning
confidence: 99%